2016
DOI: 10.21475/ajcs.2016.10.07.p7640
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salicylic acid (SA) and ascorbic acid (ASA) on in vitro propagation and salt tolerance of date palm (Phoenix dactylifera L.) cv. ‘Nersy’

Abstract: This study was carried out to investigate the antioxidant effects of salicylic acid (SA) and ascorbic acid (ASA) under two stress levels (75 and 150 mM NaCl) on growth and some biochemical constituents of date palm cv. Nersy cultured in vitro. Micro-propagated shoots of cv. Nersy at length 2.5-3 cm was excised from the proliferation medium and were separately cultured on MS medium. The data indicated that maximum growth and chlorophyll content of shoots was observed after 75 days of culturing in the medium sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…Moreover, NaSA in both tested concentrations caused, over 6.0 times higher production of carotenoids after 8 days of treatment, in comparison with C (Table 5 and Supplementary Table S4). Similarly, higher amounts, in comparison with the control, for chlorophyll a and b content had been shown before for P. dactylifera and A. aucheri shoot cultures treated with SA (Abbaspour and Ehsanpour 2016;Al-Mayahi 2016). Additionally, higher accumulation of carotenoids after elicitation with SA had also been reported for A. aucheri cultures (Abbaspour and Ehsanpour 2016).…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, NaSA in both tested concentrations caused, over 6.0 times higher production of carotenoids after 8 days of treatment, in comparison with C (Table 5 and Supplementary Table S4). Similarly, higher amounts, in comparison with the control, for chlorophyll a and b content had been shown before for P. dactylifera and A. aucheri shoot cultures treated with SA (Abbaspour and Ehsanpour 2016;Al-Mayahi 2016). Additionally, higher accumulation of carotenoids after elicitation with SA had also been reported for A. aucheri cultures (Abbaspour and Ehsanpour 2016).…”
Section: Discussionsupporting
confidence: 70%
“…As a result of our findings, the highest shoot length was obtained from the media containing ASA when antioxidants were used alone and ASA+CA combination when used together. In a study conducted by Al-Mayahi et al (2016) on persimmon, it was reported that the highest shoot length was obtained by combining ASA with salicylic acid (SA). In the study conducted by Jakhar et al (2019) on guggul (Commiphora wightii), the highest shoot length was obtained in the medium where 150-200 mg L -1 AC were added, different from our results.…”
Section: Resultsmentioning
confidence: 99%
“…When the results were examined in terms of number of leaves, the best results were obtained in 100 mg L -1 ASA used alone and 60+40 mg L -1 ASA+CA in combination with each other. Al-Mayahi et al (2016) reported that the highest number of leaves of persimmon was obtained with the combination of ASA+SA.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to being active as antibodies for the purpose of maintaining cell continuity in activity and growth (10), one of the growth regulators that use in this field is Salicylic Acid (SA), which is known to stimulate plants to resist stress, especially abiotic stresses, which belongs to the group of phenols (Phenolic Compound), which is found in plants and has a various of roles for plant growth and development, increasing the efficiency of carbon representation, transpiration, ion absorption and transporting (29). Previous studies showed that the use of salicylic acid as a spray on the shoot of the plant stimulates the growth of the palm leaf (9,4). Another application in increasing the tolerance of plants to stress is spraying with a solution of Hydrogen Peroxide (H 2 O 2 ), which is a double-edged factor as, in low concentrations, it acts as a complex molecular signal that causes the plant to endure against stress, whether biotic or abiotic (26).…”
Section: Introductionmentioning
confidence: 99%